Cytoreductive surgery with or without perioperative intraperitoneal chemotherapy for the management of peritoneal carcinomatosis: Our initial experience (Annals of Medical Research, 2021)
Aim: We studied to present our initial experience of cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) or early postoperative intraperitoneal chemotherapy (EPIC) in the treatment of peritoneal carcinomatosis. Material and Methods: The results of 20 consecutive patients treated with CRS±HIPEC or EPIC for peritoneal carcinomatosis in our hospital between November 2014 and February 2019 were evaluated retrospectively. Demographic, clinical and histopathological data of the patients were analyzed. The patients were also divided into two groups as PCI score 10 and PCI score ≥ 10 and a comparison was made between the groups.Results: There were 20 patients in our study. Fifteen patients were female and 5 were male. The mean age was 52.2±15.7 years. Primary tumor was ovarian cancer in 8 patients, colorectal cancer in 8 patients, malignant mesothelioma in 3 patients and gastric cancer in 1 patient. In the ovarian cancer group, CRS alone was applied in 4 patients, CRS+HIPEC in 3 patients and CRS+EPIC in 1 patient. All patients with colorectal cancer underwent CRS+HIPEC. Two of the patients with malignant mesothelioma were treated with CRS+HIPEC and one with CRS+EPIC. The patient with gastric cancer received CRS+HIPEC. The mean peritoneal carcinomatosis index (PCI) was 12.35±7.71. The median completeness of cytoreduction (CC) score was 0 (0-1). The mean operating time was 292.5±59.9 minutes. Perioperative morbidity was developed in 11 patients, and HIPEC-induced toxicity occured in 2 patients. Perioperative mortality was seen in 1 patient. The median overall survival was 17.7 (1.1-56) months. In addition, when two groups were compared, there was no statistically significant difference in terms of age, gender, origin of tumor, surgical method, CC score, operative time, Clavien-Dindo score, postoperative hospital stay and survival (p>0.05). Conclusion: Cytoreductive surgery and intraperitoneal chemotherapy provide satisfactory results in the treatment of patients with peritoneal carcinomatosis. Good preoperative evaluation, appropriate patient selection and multidisciplinary approach are essential for the success of the curative approach to peritoneal carcinomatosis.
Keywords: Peritoneal carcinomatosis; cytoreductive surgery; HIPEC; EPIC